Responsibility Development Efforts through Online Learning at Vocational High School - Lili Halimah; Ernandia Pandikar; Arnie Fajar; Dewi Shopiah (STAI Hubbulwathan Duri, 2022)
This study was based on the development of the times which increasingly shows attention to character education – the responsibility of students who are starting to worry about education staff and parents. Civics subjects that focus on the formation of citizens who understand and are able to carry out their rights and obligations. However, in the current state of the Corona Virus Disease 2019 (Covid-19) outbreak, it demanded to implement social restrictions and organize an activity from home through government circular number 15 of 2020. The obstacles faced in the implementation of online learning, among others, related to the readiness of human resources, limitations in facilities and infrastructure, as well as limitations in communication. This study determined the efforts to develop the character of responsibility from both teachers and students during online learning at a vocational high school in Cimahi City. This study used a qualitative approach, where the data were involving the results of interviews with teachers, curriculum representatives, and students. The results of the study, strengthening the character of responsibility can be seen from the objective conditions of online learning, lesson planning, implementation, evaluation, and school support programs, and PPKn teachers. To improve the quality of online learning, schools provide learning services according to needs during a pandemic, policy socialization is needed by teachers. curriculum representatives, as well as students. The results of the study, strengthening the character of responsibility can be seen from the objective conditions of online learning, lesson planning, implementation, evaluation, and school support programs, and PPKn teachers.